2018
DOI: 10.1128/aem.02370-17
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic Production of trans -3-Hydroxyproline in Echinocandin B Biosynthesis

Abstract: Echinocandins are antifungal nonribosomal hexapeptides produced by fungi. Two of the amino acids are hydroxy-l-prolines: -4-hydroxy-l-proline and, in most echinocandin structures, (-2,3)-3-hydroxy-(-2,4)-4-methyl-l-proline. In the case of echinocandin biosynthesis by , both amino acids are found in pneumocandin A, while in pneumocandin B the latter residue is replaced by -3-hydroxy-l-proline (3-Hyp). We have recently reported that all three amino acids are generated by the 2-oxoglutarate-dependent proline hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…Due to the lack of their respective standards, the identity of these products was not confirmed. Our observation was, however, consistent with recently reported data (Mattay et al 2018), wherein they confirmed that the major product catalyzed by Ap-HtyE was 4-Me-3-Hyp while the minor product was 3-hydroxy-4-hydroxymethyl-L-proline (4-HyMe-3-Hyp).…”
Section: Identification and Biochemical Characterization Of The Proline Hydroxylase Activity Of Ap-htye And Aa-htyesupporting
confidence: 93%
See 2 more Smart Citations
“…Due to the lack of their respective standards, the identity of these products was not confirmed. Our observation was, however, consistent with recently reported data (Mattay et al 2018), wherein they confirmed that the major product catalyzed by Ap-HtyE was 4-Me-3-Hyp while the minor product was 3-hydroxy-4-hydroxymethyl-L-proline (4-HyMe-3-Hyp).…”
Section: Identification and Biochemical Characterization Of The Proline Hydroxylase Activity Of Ap-htye And Aa-htyesupporting
confidence: 93%
“…Moreover, both Ap-HtyE and Aa-HtyE were shown to effectively hydroxylate C-3 of 4-Me-Pro in vitro, confirming their involvement in the generation of both trans-4-Hyp and 4-Me-3-Hyp. During the preparation of this manuscript, Mattay et al independently published the characterization of Ap-HtyE and reported some of the results discussed above (Mattay et al 2018). We further demonstrated that Ap-HtyE and Aa-HtyE are also capable of hydroxylating D-proline though with relatively lower efficiency.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…All these findings suggest that in pneumocandin biosynthesis, Hyp incorporation at position 6 is largely driven by the availability of Hyp substrates rather than a distinct substrate selectivity of the NRPS adenylation domain (A-domain). This is different in echinocandin B biosynthesis by A. pachychristatus : here, the proline hydroxylase HtyE produces even more 3Hyp (3Hyp/4Hyp ≈ 1:2.5–3.0; (Mattay et al 2018 ; Zhang et al 2018 )). However, 3Hyp is not found in echinocandin products.…”
Section: Structural Elementsmentioning
confidence: 97%
“…Echinocandins, a family of cyclic hexlipopeptides, are a new class of antifungal agents with broad-spectrum activity against Pneumocystis carinii, Aspergillus species, and Candida (Emri et al 2013). These compounds can disturb the biosynthesis of β-1,3-glucan in the fungal cell walls by inhibiting β-1,3-glucan synthase activity (Bauer and Bronstrup 2014;Mattay et al 2018). Thus, echinocandins have very few toxic side effects in humans because glucan polymers are not present in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%